Determinación de la línea básica de resistencia de Spodoptera frugiperda Smith a los insecticidas fipronil, permetrina, lufenuron y metomil - Vergara Burgos, Mariana Alinda (2016)
SUMMARY The work was carried out in the laboratories of Entomology of the Ability of Agricultural Sciences of the Technical University of Babahoyo, located in Km. 7,5 of the road Babahoyo-Montalvo. Insecticide four was investigated in three repetitions. The basic resistance line of Spodoptera frugiperda was determined (Smith) to the insecticide fipronil, lufenuron, permetrina and metomil, by means of the realization of bioensayos of susceptibility and selection pressure in laboratory populations. The application method was used on the loin of the larvas of the third to urge in solutions of each insecticide, during 96 hours in total. They were used between eight and ten concentrations by each insecticide, which oscillated among 0,0-10 ug/worm, respectively. Additionally, the answer of a group of larvas was evaluated (control) with feeding only. The selection pressure was carried out during a generation. The selection pressure was performed for one generation. It was concluded that the median lethal doses of the insecticides metomyl, lufenuron, fipronil and permethrin are 1.29762, 0.864843, 1.87362 and 2.39809 respectively. The DL50 oscillated of 2,1 times the commercial dose. The high control levels indicate that the worm don't still have resistance mechanisms to these insecticides, therefore they are good to implement strategies of handling of the resistance in S. frugiperda.